Efficacy and safety of rechallenge treatment with gefitinib in patients with advanced non-small cell lung cancer. (September 2016) - Cappuzzo, Federico; Morabito, Alessandro; Normanno, Nicola; Bidoli, Paolo; Del Conte, Alessandro; Giannetta, Laura; Montanino, Agnese; Mazzoni, Francesca; Buosi, Roberta; Burgio, Marco Angelo; Cerea, Giulio; Chiari, Rita; et al.
Highlights: Empiric rechallenge with gefitinib in third-line EGFR mutated-NSCLC is feasible. This strategy provides modest benefit for some patients. The driver of resistance to EGFR-TKI should be sought for each patient to tailor therapy. Abstract: Objectives: Although patients with advanced non-small cell lung cancer (NSCLC) and an activating epidermal growth factor receptor (EGFR) mutation benefit from the use of EGFR-tyrosine kinase inhibitors (TKI), most of them progress within 12 months from treatment start due to acquired resistance. In clinical practice, many physicians frequently offer these patients retreatment with EGFR-TKIs after a chemotherapy break, based on small or retrospective studies. Materials and methods: A phase II trial was conducted in patients with stage III/IV NSCLC, to assess the efficacy, safety and impact on quality of life (QoL) and disease-related symptoms of gefitinib rechallenge. Eligible patients had initially responded to first-line gefitinib and progressed after second-line chemotherapy. Results: Of 61 enrolled patients, 73.8% were female, 100% had EGFR-mutated adenocarcinoma and 67.2% were never-smokers. Thirty-two (52.5%) patients obtained a clinical benefit, with 3 (4.9%) achieving a partial response and 29 (47.5%) having stable disease. Median progression-free survival was 2.8 months, overall survival 10.2 months and duration of gefitinib treatment 3.6 months. The most common all grade-adverse events were diarrhea (27.6%), nausea and/or vomiting (20.3%), rash (14.7%) and dyspnea (10.3%); no new toxicities were apparent. Conclusion: Findings from this study indicate that gefitinib rechallenge offers modest benefit and may be taken into consideration only for patients for whom no other treatment option exists.